Calculated heat flow for the Ensenada region, Baja California, Mexico - JM Beltrán-Abaunza; AL Quintanilla-Montoya (Ciencias Marinas, 2001)
Due to the scarcity of heat flow data in the region of Ensenada, Baja California (Mexico), the present study calculated them using the silica geothermometer technique. The average heat flow value determined was 123.33 ± 35.57 mW m–2 (2.95 ± 0.85 HFU). Four zones within the study area, related to the main fault systems of the region, were found to have high hydrothermal activity. The potential use of geothermal resources in the area is feasible as it is considered a low geothermal system with water temperature values, above the static water level, that vary from 30ºC to 108ºC.